Studi Korelasional Antara Kemampuan Komunikasi Interpersonal dan Kompetensi Profesional Dengan Kinerja Guru SMA - Purwaningsih Purwaningsih (Jurnal Dewantara, 2017)
In an institution, performance is an answer or a picture of the success or failure of employees in the institution working in order to achieve the goals of the institution or organization that has been established. In this study, the authors use correlational research that puts the research variables into two groups namely independent variables and dependent variables. Based on hypothesis test result there is a positive correlation between interpersonal communication ability of principal with high school teacher performance in Metro City and there is a positive correlation between teacher professional competence with teacher performance of SMA Negeri as Metro City, with explanation that the higher professional competence of teacher will the higher the performance of teachers SMA Negeri.